Study of reasons for relapse in patients with bipolar I disorder with repeat admissions and its correlation with substance use - Megha Maghade; Abhishek Somani; Anand Saoji; Vivek Kirpekar (Asian Journal of Medical Sciences, 2022)
Background: Mood disorder is one of the common causes, for which psychiatric consultations are sought. A better understanding of the factors that lead to repeated admissions, increased relapse rates, and concurrent substance dependence is necessary for the development of interventions that may reduce the likelihood of adverse effects in patient with bipolar I disorder. Aims and Objectives: The aims of this study were as follows: (1) To study the correlation between the reasons for relapse and substance use with various sociodemographic factors in patients having bipolar I disorders and (2) to find out the correlation between reasons for relapse, substance use, and severity of illness. Materials and Methods: This was a cross-sectional single interview study, in which 67 consecutive patients having bipolar I disorder and admitted in psychiatry ward were admitted on the basis of a pre-defined inclusion and exclusion criteria. The details about psychiatric, relapse-related symptoms, substance use-related symptoms, as well as other aspects of clinical profile were taken. Results: Out of 67 patients, 51 (76.1%) were male and 16 (23.8%) were female. Mean age of the participants was 30.43 years (S.D.=9.05). Sleep disturbance was seen in all patients (67) and was also the most common symptom. It was followed by psychomotor disturbances in 60 (89.5%) of the patients. Among 67 patients included in the study, substance use was seen among 28 (41.7%) of the patients. Substance use was significantly associated with age of the patients and occupation (P=0.03 each). The age group of more than 30 years (57.7%) had significantly higher substance use compared to those <30 years (31.7%). Conclusion: Concurrent substance use is associated with increased risk of relapse and readmissions in cases of patients with bipolar I disorders. A thorough history is necessary to rule out substance use in these cases.